2022
DOI: 10.3390/s22155869
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sufficient Sensor Node Embedding 2D Visible Light Positioning through a Solar Cell Module

Abstract: Nowadays, indoor positioning (IP) is a relevant aspect in several scenarios within the Internet of Things (IoT) framework, e.g., Industry 4.0, Smart City and Smart Factory, in order to track, amongst others, the position of vehicles, people or goods. This paper presents the realization and testing of a low power sensor node equipped with long range wide area network (LoRaWAN) connectivity and providing 2D Visible Light Positioning (VLP) features. Three modulated LED (light emitting diodes) sources, the same as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Figure 14 shows the relationship between the relaxation time obtained from the cutoff frequency where the conductivity changes from a constant value in the Bode diagram (plateau) to increasing with frequency increase for all temperatures. In such circumstances, such as is observed here in the case of CuCoO2_H (see Figure 12c) for all temperatures, according to the power low model, the real part of the conductivity σ′(ω,T) can be expressed in terms of dc-conductivity σdc and the hopping diffusion rate of protons ωH ≈ 1/τ (in this case) as [94] σ'(ω, T) = σ 1 + (5) where n is an exponent with a value between 0 and 1 and is related to interactions between mobile ions (H + in our case) and the dimensionally of the conduction pathway [97]; for instance, this occurs in polymer electrolytes of P[VBTC][Cl]80-ran-PMMA20 at different temperatures (303 K to 363 K) and P[VBTC][TFSIl]80-ran-PMMA20 at (308 K to 378 K), respectively [98]. From the fit of the real part of the conductivity shown in the Bode diagrams in Figure 12, we have obtained the values of sample relaxation time; these values are plotted in Figure 14 for each temperature.…”
Section: Dielectric Spectra Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…Figure 14 shows the relationship between the relaxation time obtained from the cutoff frequency where the conductivity changes from a constant value in the Bode diagram (plateau) to increasing with frequency increase for all temperatures. In such circumstances, such as is observed here in the case of CuCoO2_H (see Figure 12c) for all temperatures, according to the power low model, the real part of the conductivity σ′(ω,T) can be expressed in terms of dc-conductivity σdc and the hopping diffusion rate of protons ωH ≈ 1/τ (in this case) as [94] σ'(ω, T) = σ 1 + (5) where n is an exponent with a value between 0 and 1 and is related to interactions between mobile ions (H + in our case) and the dimensionally of the conduction pathway [97]; for instance, this occurs in polymer electrolytes of P[VBTC][Cl]80-ran-PMMA20 at different temperatures (303 K to 363 K) and P[VBTC][TFSIl]80-ran-PMMA20 at (308 K to 378 K), respectively [98]. From the fit of the real part of the conductivity shown in the Bode diagrams in Figure 12, we have obtained the values of sample relaxation time; these values are plotted in Figure 14 for each temperature.…”
Section: Dielectric Spectra Analysissupporting
confidence: 52%
“…In recent decades, there has been a significant demand for advancements in the integration of high-efficiency p-type transparent conductive oxides (TCOs) into industrial applications, particularly in the past few decades [ 1 , 2 , 3 , 4 , 5 ]. However, the research community is keen on exploring alternative TCOs and enhancing their electrical and optical properties to improve device efficiency [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 40×40 cm test area, average errors around 3 cm using third-order regression algorithms [219] and a median error below 2 cm using neural networks [218] are reported, but using a very dense (10 cm) training grid. In [220], a simple trilateration approach is used. The contributions of the three LEDs -modulated at distinct frequencies around 1 kHz-are demultiplexed at a single solar cell receiver having a bandwidth of 3.5 kHz.…”
Section: Physical Properties Of Receiversmentioning
confidence: 99%
“…For energy-constrained applications, it has been shown that the use of solar cell receivers allows for a dual positioningenergy harvesting functionality [220]. While the bandwidths of solar cell receivers are sufficient to demultiplex LED signals modulated at different frequencies [218], [220], the obtained signal-to-noise ratios under normal illumination levels have also proven to be sufficient to obtain a reasonable accuracy.…”
Section: ) Solar Cell Receivermentioning
confidence: 99%
See 1 more Smart Citation